Sistem Pakar Menggunakan Metode Certainty Factor untuk Estetika Kulit Wanita dalam Menjaga Kesehatan - Subrianto Chandra; Yuhandri Yunus; Sumijan Sumijan (SEULANGA SYSTEM PUBLISHER, 2020)
The skin is an important organ located on the outside of the human body that needs to be kept healthy. Good skin health will certainly increase self-confidence, especially for women. Lack of information about diseases and treatment solutions and the small number of professional estheticians means that women end up not consulting when skin problems arise. If left untreated, skin problems will be more serious. The purpose of this study was to identify the accuracy of skin problems in women so that a solution in caring for the skin was obtained. The data processed in this study are the results of an interview from an aesthetic doctor about skin problems in women and the solutions and symptoms experienced by patients. Then the data obtained manually were processed using the Certainty Factor method and tested with a website-based system. The processing stage of this method is the compilation of symptoms into rules, giving weight values ​​for each symptom and calculating based on the Certainty Factor rule formula. The results of testing this method were 13 data on aesthetic skin diseases identified from 15 trial data. So that the level of accuracy is 86.67%. The results of this test have been able to identify well. The Certainty Factor method used can identify quite specifically and can be recommended to skin aesthetic doctors in increasing accuracy for identifying skin problems in women.